THE INFLUENCE OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE TURNOVER INTENTION (Study at PT. Kawanua Dasa Pratama/Freshmart Superstore Manado) - Luntungan, Vincencia Maggy; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Turnover is commonly problem faced in PT. Kawanua Dasa Pratama (Freshmart Superstore) Manado. Turnover intention comes up as a plan to quit from company. Most of the turnover brought an adverse influence on the organization, both in terms of cost and in loss of time and chance to take advantage of opportunities. High job satisfaction and organizational commitment will reduce employee turnover intention rates from company. This research aims to find out how job satisfaction and organizational commitment can affect the turnover intention of employee in PT. Kawanua Dasa Pratama (Freshmart Superstore) Manado. Multiple regressions model is used to answer the research problem. The total sample for this research is 100 employees, and questionnaire had been using to obtain the information. The research findings show that the independent variable job satisfaction and organizational commitment had a negative significant influence to employee turnover intention simultaneously and partially. The management of Freshmart Superstore Manado may consider about the satisfaction of employees, such as the salary, promotion, and also appreciation for their work. Keywords: job satisfaction, organizational commitment, employee turnover intention